QuEChERS LC–MS/MS Screening Method for Mycotoxin Detection in Cereal Products and Spices - Pantano, Licia (Int J Environ Res Public Health, 2021)
We developed and validated a screening method for mycotoxin analysis in cereal products and spices. Ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC–MS/MS) was used for the analysis. Dispersive solid-phase extractions (d-SPEs) were used for the extraction of samples. Ochratoxin A (OTA), zearalenone (ZEA), aflatoxins (AFLA; AFB(1), AFB(2), AFG(1), AFG(2)), deoxynivalenol (DON), fumonisin (FUMO; FB(1), FB(2), FB(3)), T2, and HT2 were validated in maize. AFLA and DON were validated in black pepper. The method satisfies the requirements of Commission Regulation (EC) no. 401/2006 and (EC) no. 1881/2006. The screening target concentration (STC) was under maximum permitted levels (MLs) for all mycotoxins validated. The method’s performance was assessed by two different proficiencies and tested with 100 real samples.